New normal behavior toward the Covid 19 transmission - Eppy Setiyowati; Ni Njoman Juliasih; Reny Mareta Sari (Alma Ata University Press, 2021)
Background: The high level of knowledge, postive attitude and community behavior in breaking the chain of transmission of Covid 19 became the foundation to stop the Covid 19 disease outbreak in East Java, Indonesia, showing the high rate of Middle East Respiratory Syndrome-Coronavirus (MERS-CoV) infection due to the Covid 19 disease. The public still does not understand about Covid 19 disease, corona virus, corona virus distribution chain, and breaking the chain of spread and transmission of the corona virus. The purpose of the study: the study conducted an analysis of new behavioral changes to the spread of covid 19. Research method: The analysis study was conducted with a crossectional approach, in a population conducted in a random selection of 250 participants in three locations (Sidoarjo city, Surabaya City and Mojokerto City). Measurement of behavior change includes knowledge, attitudes and actions. Data collection through questionnaires distributed with google form through whats-app group. Data processing through statistical analysis is a cryptic test and a statistical test. Statistical tests are conducted with linear regression. Research results: Based on the results of the liner regression test, the results of the study show sociodemographic to knowledge; age > 0.01; gender. >0.01; employment, <0.01; Education <0.01, it shows that age and gender are not related to knowledge related to covid 19. Sociodemography statistics test results with attitudes show; age > 0.01; gender. >0.01; employment, <0.01; Education <0.01. The results of this statistical test show that sociodeography of age and gender is not related to knowledge in understanding the spread of covid 19 disease. Sociodemography statistical test results with practice actions: age > 0.01; gender. ,0.01; occupation, <0.01; Education <0.01. The results of this statistical test showed that sociodemoigraphy age is not connected with knowledge in understanding the spread and disconnection of the covid 19 chain. Conclusion: This study reflects the importance of health education as a cornerstone element in improving KAP against Covid 19 infection in preventing the spread of viruses and disease outbreaks. in improving KAP against Covid 19 infection in preventing the spread of viruses and disease outbreaks.